PEMBUATAN TEH HERBAL DARI DAUN KELOR (Moringa oleifera) UNTUK MENINGKATKAN KESEHATAN TUBUH - Hakim, Muhamad Shaufil; Sari, Ainayya Amalia; Al Aqad, Yuniar Rizki Rahmawati; Amara, Nadya; Putri, Aida Musyarrifah Hasri; Putra, Muhammad Septian Dwi; Sani, Nabila Aulia; Khaerunnisa, Khaerunnisa; Darmawan, Adi; Susanto, Oki Novian; Rosmaliati, Rosmaliati (Universitas Mataram, 2023)
Moringa is a type of plant that belongs to the Moringaceae family. This plant is also known as (Moringa oleifera). Moringa has many uses and has long been used by various cultures because various parts of this plant have high nutritional value and health properties that are considered beneficial. Some parts of the Moringa plant that are commonly used are the leaves, fruit, flowers, seeds, and roots. Moringa (Moringa Oleifera) originates from India and Arabia and then spreads to various regions. years, and withstand extreme heat conditions. This plant comes from tropical and subtropical regions of South Asia. In Indonesia, Moringa trees are widely planted as living fences, planted along fields or on the edges of rice fields, functioning as green plants. In addition, the Moringa plant is also known as a nutritious medicinal plant by utilizing all parts of the Moringa plant, starting from the leaves, bark, seeds, to the roots. This plant has been studied for its health benefits, has antifungal, antioxidant, antibacterial, anti-inflammatory, diuretic, and as a hepatoprotector. According to Folid, Moringa leaves can be consumed as a vegetable, consumed in the form of Moringa leaf tea, flour, powder or Moringa leaf capsules. Moringa leaf tea is a caffeine-free herbal tea which is very good for health and has a pretty good taste. Moringa leaf tea contains many nutrients that can increase the body's metabolism. Tea is a drink prepared by soaking the leaves or certain parts of the tea plant (Camellia sinensis) in hot water. This tea plant is the main source for various types of tea known throughout the world. There are several main types of tea that are produced from the Camellia sinensis tea plant, and these differences are mainly derived from the processing of the tea leaves.